Aktivitas Antibakteri Masker Gel Peel-Off Berbahan Lamun Enhalus acoroides Terhadap Staphylococus aureus - Suci Yanti Adam; Rieny Sulistijowati; Fernandy M. Djailani (Jambura Fish Processing Journal, 2026)
Enhalus acoroides seagrass has potential as a natural antibacterial agent because it contains flavonoid and alkaloid compounds that can inhibit the growth of Staphylococcus aureus bacteria. This study aimed to formulate and characterize a peel-off gel mask containing E. acoroides extract as a natural antibacterial agent. The research procedures included the extraction of bioactive compounds from seagrass, the preparation of peel-off gel masks with various extract concentrations, and antibacterial activity testing against S. aureus using the disc diffusion method. In addition, pH and homogeneity tests of the formulations were also conducted. The study employed a Completely Randomized Design (RAL) with one treatment consisting of four extract concentration levels, namely 0 mL, 10 mL, 15 mL, and 20 mL, with three replications for each treatment. The results showed that differences in extract concentration had a significant effect (p0.05) on the antibacterial activity of the peel-off gel mask. The inhibition zone diameters ranged from 8.15 mm to 11.80 mm. The homogeneity test indicated that all formulations had a uniform texture without coarse particles. The pH test demonstrated that the mask formulations had a significant effect (p0.05), with pH values ranging from 6.11 to 6.67. These values were within the standard pH range for peel-off gel masks and were considered safe for skin application. Formulations containing 15 mL and 20 mL of extract exhibited the highest antibacterial activity, categorized as strong, with inhibition zone diameters of 10.19 mm and 11.80 mm, respectively. The antibacterial activity was presumed to be associated with the presence of flavonoid and alkaloid compounds that possess bacteriostatic properties. Based on the findings, the peel-off gel mask containing Enhalus acoroides extract has the potential to be developed as a natural antibacterial cosmetic product.